(untitled) (Rudarsko-geološko-naftni zbornik, 2021)
Pebbles taken from the bed of the Cretaceous Abeokuta Formation paraconglomerate near the Oluwa River were used to infer the depositional setting and the nature of the source area, through the integration of bivariate and ternary (sphericity-form and Zingg diagrams) analyses. Deposition in a river environment is indicated by the high sphericity values, ranging from 0.59 to 0.88 (average 0.70). Also, bivariate plots of the maximum projection sphericity (ψp) vs. oblateprolate index (OPI) and flatness index (FI) vs. maximum projection sphericity (ψp) point to the domination of fluvial processes. Dominantly elongated, compact elongated, compact and compact-bladed pebbles are typical for sedimentary regime with prevalence of fluvial over beach processes. Co-existence of various pebbles shapes (mainly disc, rod-, and sphere-shaped), despite of the similar, predominantly quartz composition, may occur due to the different clast fabrics. This heterogeneity also indicates various transport distances and water energies, pointing to the multiple source areas.